Choice of factor VIII/IX regimen in adolescents and young adults with severe or moderately severe haemophilia. A French national observational study (ORTHem 15-25). Issue 151 (March 2017) - ; Borel-Derlon, Annie; Borg, Jeanne-Yvonne; Chambost, Hervé; Claeyssens, Ségolène; d'Oiron, Roseline; Gay, Valérie; Girault, Stéphane; Goudemand, Jenny; Gruel, Yves; Guillet, Benoit; Hassoun, Abel; et al.
Abstract: Introduction: The value and challenges of long-term prophylaxis (LTP) in adolescents and young adults need further characterisation. Aim: To determine the proportions of adolescents and young adults with severe or moderately severe haemophilia in France under LTP and treatment on demand (OD). Methods: Patients 15 to 25 years old with haemophilia A or B, factor VIII/IX ≤ 2% and no current inhibitor could be included if they had been under factor VIII/IX treatment at least 12 months and kept a treatment and bleeding diary. Results: LTP was administered to 169/212 patients (79.7%) and OD treatment to 40/212 patients (18.9%). The most frequent reasons for initiating LTP were joint bleeding, target joints and frequent bleeds; whereas OD treatment was most often selected on the basis of mild bleeding phenotype or because of constraints on LTP. The mean annual bleed rate (ABR) in the OD group (6.33) was higher than in the LTP group (3.07, p < 0.001). Mean ABR did not differ significantly between age strata (15–18, > 18–21 and > 21–25 years), but was significantly higher for patients with severe haemophilia (4.02) as compared to those with moderate haemophilia (1.97, p = 0.002). No significant difference was observed in mean ABR for joint bleeds between the LTP and OD groups. Physician reported LTP compliance was good or excellent in 97.0% of patients. Conclusion: LTP is the predominant factor VIII/IX treatment among adolescents and young adults with severe or moderately severe haemophilia in France. LTP was associated with low ABR and high compliance. Highlights: 80% of 15–25 years old severe or moderately severe haemophilia patients received prophylactic treatment. Their compliance rate was high (61% to 86%). Their bleeding rate was low (ABR 3.07).